Transparent conducting oxide films with p-type characteristics derived from sol-gel dip-coating of LaF3- and CeF3-doped tin oxides - Dao, Van-Da; Tran, Quang-Phu; Pham, Van-Hoi (Vietnam Journal of Science and Technology, 2025)
Transparent semiconductor oxide films, typically based on doped indium tin oxide, find widespread use in optoelectronic devices. Tin oxide films inherently exhibit n-type conductivity. Achieving efficient p-type tin oxide film electrodes is a challenging task for applications in p-n based photonic devices. In this investigation, we introduce innovative p-type transparent films whose optical transmittance and electrical conductivity can be adjusted by doping tin oxide films with various rare-earth triflouride compouds such as LaF3 and/or CeF3 using sol-gel dip-coating method. The p-type conductance of the thin films is confirmed through Hall effect and Seebeck coefficient measurements. The results obtained indicate that the LaF3- and CeF3-doped SnO2 film exhibits a transmittance of 85.1% and 80.9% at a wavelength of 550 nm, a low electrical resistivity of 8.68 × 10–3 Ωcm and 1.70 ´ 10–2 Ωcm, and a high figure-of-merit of 6.59 × 10–4 Ω⁻¹ and 1.74 ´ 10–4 Ω⁻¹, respectively, making them highly suitable for applications in optoelectronics.